Prevalence of associated psychosomatic symptoms in patients of irritable bowel syndrome - Habib, Anwar; Ahmad, Razi; Rehman, Sana (International Journal of Advances in Medicine, 2018)
Background: Irritable bowel syndrome (IBS) is a functional disorder of gastrointestinal tract with unclear aetiology and no reliable biomarkers like other chronic and functional disorders. Majority of the patients of IBS suffer from various forms of psychosomatic disorders as comorbidity that further exaggerate the complexity of diagnosis and management of IBS. The aim of the present study was to find the prevalence of commonly associated psychosomatic symptoms associated with IBS in the patients of lower socioeconomic strata. Methods: This is a prospective observational study carried out over a period of 10years from November-2007 till October-2017, in HAHC hospital attached to Hamdard Institute of Medical Sciences and Research. A structured questionnaire comprising of a total of 36 closed ended questions was designed. Eleven questions were about the demographic characteristics and twenty-five were pertaining to IBS symptoms according to Manning and Rome III criteria with some necessary modifications. Various psychosomatic illnesses were recorded separately after ruling out the organic cause with appropriate investigations. Results: In the present study out of 4000 patients with IBS symptoms, 70.8% were having some form of psychosomatic symptoms, Patients with psychosomatic disorders were significantly more often young in age and females (53.28%), showing highest number of patients belonging to the age group 26-35years (51.44%). 34% patient had two or more psychosomatic illnesses. Headache (62.26%) and insomnia (63.03%) were the commonest followed by chest pain (36.54%). Chest pain (77.68%), headache (62.26%) and insomnia (56.07%) was more common in male whereas palpitation (60.58%) and breathlessness (57.68%) was more common in female. Conclusions: There is significantly high prevalence of psychosomatic illness in the patients of IBS in the low socio-economic strata. The young patients (productive age group) are more affected which may be responsible for further deteriorating their social and economic condition.